PEMBUATAN MODUL PEMBELAJARAN INTERAKSI MANUSIA DAN KOMPUTER BERBASIS ANDROID (STUDI KASUS : PRODI TEKNIK INFORMATIKA ILMU KOMPUTER UUI) - Karmina, Rudi (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2014)
To find the website at Baitul Mal Aceh, including the main window of public disclosurein accordance with the needs of the user community and to improve the website inBaitul Mal Aceh as a public information center, How to Baitul Mal Aceh provideinformation to the public, and how to use the website as a window The main publicdisclosure. Website user research as the main window of public disclosure in the BaitulMal Aceh Percentage Quantitative research methods. T-test and multiple linearregression is done by collecting data, presenting and analyzing data using test-t.Techniques analysis of data processing in this study using computational calculationsSPSS 16.0 (Statistical Package for Social Science). Based on multiple linear regressioncalculation, it is known that the Beta coefficient (Î²) of 0.815. This means that 81.5% ofthe variation variables can be explained in website accessibility, usefulness websiteaccess, behavior user website, and the information obtained from the website, while therest, namaly 18.5% is explained by other variables not examined in this study.Keywords: Website, window, openness, information, Baitul Mal Aceh